Gonadotropin-Releasing Hormone Receptor-Targeted Near-Infrared Fluorescence Probe for Specific Recognition and Localization of Peritoneal Metastases of Ovarian Cancer - Liu, Qiyu; Zhou, Xiaobo; Feng, Wei; Pu, Tao; Li, Xiaoping; Li, Fuyou; Kang, Yu; Zhang, Xiaoyan; Xu, Congjian (Frontiers in Oncology, 2020)
Background: The completeness of cytoreduction is an independent prognostic factor for advanced ovarian cancer. Successful cytoreduction rely on the accurate recognition and localization of cancerous lesions. The combination of intraoperative fluorescence imaging and tumor-targeted near-infrared probe might improve staging and surgical completeness. A promising target for ovarian cancer is gonadotropin-releasing hormone receptor (GnRHR). This study aimed to develop a GnRHR-targeted imaging probe for the detection of peritoneal metastases of ovarian cancer. Methods: Indocyanine green (ICG) was conjugated with GnRH antagonist peptide to develop an ovarian cancer-selective fluorescence probe GnRHa-ICG. GnRHR expression was detected in ovarian cancer tissues. The binding capacity of GnRHa-ICG and ICG was detected in both cancer cell lines and mouse models of peritoneal metastatic ovarian cancer using fluorescence microscopy, flow cytometry and near-infrared fluorescence imaging. Results: Tissue microarray analysis revealed the overexpression of GnRHR in ovarian cancer. The binding capacity of GnRH-ICG was confirmed in a panel of cancer cell lines with different expression levels of GnRHR. GnRHa-ICG showed specific binding to peritoneal metastases in ovarian cancer mouse models. The fluorescence signal of peritoneal metastases peaked in intensity at 2 h and maintained for up to 48 h. ICG also existed a weak signal in tumor due to the EPR effect, but the intensity decreased quickly within 48 h. Moreover, GnRHa-ICG showed few fluorescence signals in intestine and was cleared mainly through liver pathway. In comparison, ICG showed high fluorescence in both liver and intestine, indicating a liver-intestine clearance. Conclusions: The developed GnRHR-targeting imaging agent GnRHa-ICG could specifically recognize metastasis lesions from peritoneal normal tissues and intestine tissues, and the modification of GnRHa improved the capacity of ICG for tumor imaging. The plateau period of GnRHa-ICG specific accumulation might be feasible for clinical applications in fluorescence-guided surgery. Our GnRHR imaging concept might also be effective in other hormone-related tumors with upregulated GnRHR expression.